Treaties between Nepal and her Neighbors: A Historical Perspective - Uprety, Prem (Tribhuvan University Journal, 2010)
Not available. Key words: Treaties; Nepal and her neighbours; Historical perspective Tribhuvan University Journal Vol. XIX, 1996 Page: 15-24 Uploaded Date: 22 Nov., 2010